Thermophysical properties of dilute acid slurries of cassava bagasse as a function of biomass loading, acid concentration, and temperature - Polachini, Tiago Carregari [UNESP] (2021)
For suitable design of equipment and process optimization, the determination of thermophysical properties of the raw materials is necessary. Therefore, this work was aimed at determining and modeling the density, specific heat, thermal diffusivity, and thermal conductivity of acid slurries of cassava bagasse used during its conversion into bioethanol. Experimental measurements were carried out in slurries with different mass fractions of cassava bagasse (0.00 to 0.10) and phosphoric acid (0.00 to 0.10) at temperatures from 278.13 to 318.13 K. Results obtained show that density varied from 986.5 to 1,029.3 kg∙m−3, specific heat from 3,830.0 to 4,142.6 J∙kg−1∙K−1, thermal diffusivity from 0.9624 × 10−7 to 1.5249 × 10−7 m2∙s−1 and thermal conductivity from 0.3825 to 0.6212 W∙m−1∙K−1. While density increased with increasing solids and acid content at decreasing temperature, the thermal properties decreased at higher solids and acid content and increased when heating the slurries. The values were well-fitted to polynomial models with good accuracy (R2 > 0.921 and MRE < 1.75%), allowing the application of the models to obtain reliable and ready-to-use data for cassava bagasse processing. Thus, the data reported in this study can be used for designing and managing momentum, heat and mass transfer processes for enhancing bioethanol production from cassava bagasse.